2017
DOI: 10.1080/14763141.2017.1285347
|View full text |Cite
|
Sign up to set email alerts
|

Effects of structural components of artificial turf on the transmission of impacts in football players

Abstract: The third generation of artificial turf systems (ATS) has matched the mechanical behaviour of natural grass, but today a high heterogeneity at structural level and mechanical behaviour in the new ATS also exists. The objective was to analyse the effect of the structural components of ATS football pitches and running speed on the capacity of impact attenuation. A total of 12 athletes were evaluated at three speed conditions (3.33 m/s, 4 m/s and maximum speed) on four different ATS, classifying them by their com… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2

Citation Types

1
15
0

Year Published

2018
2018
2023
2023

Publication Types

Select...
6

Relationship

2
4

Authors

Journals

citations
Cited by 12 publications
(16 citation statements)
references
References 25 publications
1
15
0
Order By: Relevance
“…A 12 minutes standard warm up was done before the running rhythms familiarization phase. Then, the participants tested the running rhythms established except the maximum speed run, until they felt comfortable with the conditions of the study 20 . Three repetitions for each speed in a randomized order was done within 20 m of the middle of the pitch.…”
Section: Methodsmentioning
confidence: 99%
See 2 more Smart Citations
“…A 12 minutes standard warm up was done before the running rhythms familiarization phase. Then, the participants tested the running rhythms established except the maximum speed run, until they felt comfortable with the conditions of the study 20 . Three repetitions for each speed in a randomized order was done within 20 m of the middle of the pitch.…”
Section: Methodsmentioning
confidence: 99%
“…Photoelectric cells (Microgate, Bolzano, Italy), positioned along 5 m in the middle of the 20 m pitch, was employed to control the speed. The accelerometer signal was registered during 5 s making this register coincide with running past the photocells to guarantee speed stability and avoid moments of initial acceleration and final deceleration of the test 20,50 . A ± 5% speed deviation was allowed during each speed condition.…”
Section: Methodsmentioning
confidence: 99%
See 1 more Smart Citation
“…However, each variation of playing surface will having specific characteristics and mechanical properties, 3 with implications for mechanical loading and subsequent risk of injury. 4 Reviews of the literature have typically reported no difference in overall incidence rates between natural and artificial playing surfaces. 5,6 However, the incidence of ankle injuries has been associated with an increased risk on artificial surfaces.…”
Section: Introductionmentioning
confidence: 99%
“…Three surfaces are considered to reflect the evolution of artificial turf surfaces, and to acknowledge that each variation of playing surface will have specific characteristics and mechanical properties and, 21 in turn, specific mechanical responses and subsequent risk of injury. 22 In addition to the traditional C7 placement of the MEMS devices, mechanical loading will also be quantified at the mid-tibia (in order to prevent restriction of ankle joint function during the tasks) of both lower limbs.…”
mentioning
confidence: 99%